Proceedings of the 3rd International Conference on Economics, Business and Economic Education Science, ICE-BEES 2020, 22-23 Jul 2021
DOI: 10.4108/eai.22-7-2020.2307931
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Size of Public Accounting Firms (KAP) and Specialist Auditors on Audit Quality with the Audit Committee as a Moderating Variable

Abstract: The audit quality becomes important in the realization of good corporate governance. There are several things that affect audit quality, namely the size of public accounting firm (KAP), specialist auditors, audit tenure, and so on. This study examines the influence of KAP size and specialist auditors on audit quality in banking companies in Indonesia. Furthermore, this study has a novelty on the use of audit committee variables as a moderating variable. The sample of this study is the audit report of banking c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
0
0
2
Order By: Relevance
“…Dengan demikian, KAP besar ini memiliki kecenderungan akan dapat menaikkan independensi dalam memberikan layanan jasa audit yang lebih bermutu. Penelitian yang dilaksanakan Hidayah et al, (2021) dan Purwanto, (2021) ini menyebutkan bahwa KAP yang memiliki keterkaitan dengan KAP Big 4 ini tidak serta merta memberi kualitas audit yang unggul diperbandingkan dengan KAP yang tidak memiliki hubungan dengan KAP Big 4, dengan ini didapatkan bahwa variabel ukuran KAP ini tidak memberi pengaruh terhadap kualitas audit.…”
Section: Submission Date: July 2022unclassified
See 1 more Smart Citation
“…Dengan demikian, KAP besar ini memiliki kecenderungan akan dapat menaikkan independensi dalam memberikan layanan jasa audit yang lebih bermutu. Penelitian yang dilaksanakan Hidayah et al, (2021) dan Purwanto, (2021) ini menyebutkan bahwa KAP yang memiliki keterkaitan dengan KAP Big 4 ini tidak serta merta memberi kualitas audit yang unggul diperbandingkan dengan KAP yang tidak memiliki hubungan dengan KAP Big 4, dengan ini didapatkan bahwa variabel ukuran KAP ini tidak memberi pengaruh terhadap kualitas audit.…”
Section: Submission Date: July 2022unclassified
“…Ukuran KAP yang diukur menggunakan jumlah partner dalam penelitian ini tidak terbukti dapat memengaruhi kualitas audit. Hasil penelitian ini sejalan dengan penelitian yang dilaksanakan Purwanto, (2021) dan Hidayah et al, (2021) yang menyatakan bahwa ukuran KAP tidak berpengaruh terhadap kualitas audit. Afiliasi KAP dengan banyak mitra tidak serta merta menghasilkan kualitas audit yang tinggi.…”
Section: Pengaruh Ukuran Kap Terhadap Kualitas Auditunclassified
“…However, a company's ability to attract accounting or finance specialists depends on the effectiveness of its governance requirements (Raghavan, 2022). According to (Hidayah et al, 2021), the inclusion of specialized managers within the audit committee has a positive impact on the committee's effectiveness in fulfilling its oversight role. (Anderson et al, 2004) have demonstrated that an increase in the audit committee's expertise leads to a reduction in debt costs, thereby enhancing company performance.…”
Section: Audit Committee Financial Expertsmentioning
confidence: 99%
“…Sebuah penelitian yang dilakukan di Indonesia menguji pengaruh ukuran KAP dan auditor spesialis terhadap kualitas audit pada perusahaan perbankan. Hasil penelitian menunjukkan bahwa spesialisasi auditor berpengaruh negatif terhadap kualitas audit (Hidayah et al, 2021).…”
Section: Pendidikan Akuntansi Terhadap Kualitas Auditunclassified